Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region - Kluge, Nikita J.; Novikova, Eugenia A. (Zootaxa, 2017)
Two new species, Anafroptilum orthostylus sp. n. and Anafroptilum odontostylus sp. n. are described from Thailand based on imagoes reared from larvae. Both new species lack hind wings; larvae of both species have an unusual prominent spine near cercus apex; other characters, especially shape of male imaginal gonostyli and shape of larval tergalii, are quite diverse in these two species. The genus Anafroptilum, hitherto known from the East Palaearctic [as a single species A. kazlauskasi (Kluge 1983)] and from Nearctic [as eight species reported by Jacobus & Wiersema (2014)], is reported from Oriental Region for the first time.